A young healthy male with syncope and complete heart block. Issue 2 (May 2013) - Chauhan, V; Chauhan, N; Chauhan, CGS; Vaid, M
Introduction: It is rare to see heart block as the first-and-only presentation of Lyme disease, the reported incidence being just 1% in untreated patients. Case presentation: We report a patient who presented with syncope secondary to a fluctuating heart block. He had no previous manifestations of Lyme disease. Lyme carditis was suspected after the other usual etiologies of heart block were ruled out. Later, serologies came positive and patient's heart block resolved on ceftriaxone therapy. Conclusion: In at-risk individuals, clinicians should rule out this readily-treatable cause of heart block before proceeding with permanent pacemaker implantation due to enormous clinical and cost implications involved. Missing the diagnosis also exposes the patient to the risk of developing the late complications of Lyme disease. Diagnosis of isolated Lyme carditis is a challenge because the clinician does not have the diagnostic-clues that can usually be gleaned from the more common stigmata of Lyme disease.